Carbon Deposition from the CO2-Steam Reforming of Methane Over Modified Ni/gamma-Al2O3 Catalysts - Choi, Bong Kwan; Ok, Hye Jeong; Moon, Dong Ju; Kim, Jong Ho; Park, Nam Cook; Kim, Young Chul (AMER SCIENTIFIC PUBLISHERS, 2015)
The aim of this work is to study the catalytic activity and suppression of carbon deposition in the CO2-Steam reforming of methane (SCR) to develop a high performance catalyst for GTL-FPSO application which is required to high pressure (20 bar) for F-T synthesis. Ni/La-X(6)/Al2O3 (X = Ce, Mg, Zr) catalysts were prepared by the impregnation method. The catalytic reaction was studied in a fixed bed reactor system at high pressure. X-ray diffraction (XRD), BET specific surface area and H-2-temperature programmed reduction (TPR) were used to observe the characteristics of the prepared catalysts. The carbon deposition and the carbon amount in the used catalysts were examined by SEM and TGA, respectively. As a result, it was found that the Ni/La-Mg(6)/Al2O3 catalyst showed the highest activity and high carbon resistance. The highest activity in Ni/La-Mg(6)/Al2O3 was attributed to the proper Mg loading. It also had the lowest Ni particle and formed relatively stable MgAl2O4, which have an effect on the catalytic activity.
Keywords: STEAM; DIOXIDE; GAS; CH4